Three new species of Kerria (Hemiptera: Coccoidea: Tachardiidae) from India - Ahmad, Ayashaa; Ramamurthy, V. V.; Sharma, K. K.; Mohanasundaram, A.; Vidyarthi, A. S.; Ramani, R. (Zootaxa, 2013)
Three new species of Kerria Targioni-Tozzetti from India, namely Kerria pennyae Ahmad & Ramamurthy sp. nov. on Schleichera oleosa from Orissa, Kerria dubeyi Ahmad & Ramamurthy sp. nov. on Ficus bengalensis from Bangalore and Kerria varshneyi Ahmad & Ramamurthy sp. nov. on Ziziphus mauritiana from Punjab are described and illustrated, and a key is provided to species of Kerria known from India.